Piano Learning Techniques by Agra Dipoardhi for ADHD and Autism Children at Gita Nada Music Course - Revlin Ayu Harfianti, Claudia; Sugito, Tomy Agung (Solah, 2025)
: This research examines Agra Dipoardhi's piano learning technique for children with ADHD and Autism at Gita Nada Music Course. The background is the lack of studies on effective methods for these children, despite the potential for music to improve their quality of life. These children face challenges with fine motor skills, concentration, and abstract comprehension in music. The purpose of this study was to identify Agra Dipoardhi's specific techniques, analyze their impact on piano playing ability, and her strategies to overcome learning barriers. Using a descriptive case study qualitative approach, data was collected through interviews, observations, and documentation, then analyzed by reduction, presentation, and conclusion drawing, and validated by triangulation. The results show that Agra Dipoardhi applies very specific and adaptive techniques. For ADHD students, strategies such as varied short sessions, multisensory approaches, and visual aids improve focus, self-control, and perseverance. For students with autism, an emphasis on clear structure, predictability, pattern recognition, and visual communication builds resilience and confidence. Patience, flexibility, individualization and parental collaboration are key. The application of these techniques had a significant positive impact on the piano playing ability, attitude, and musical understanding of children with special needs. This research is expected to inspire an inclusive music curriculum.